From crisis to resilience: food security policy development in Qatar - Abdulfatah Mohamed; Charlotte Salmon; Bushra Faizi; Bushra Faizi; M. Evren Tok (Frontiers in Sustainable Food Systems)
This paper delves into Qatar’s evolving food security program, emphasizing the role of state-driven capital in shaping its corporate food regime. Previously, most studies on food regimes centered on corporate dynamics and neoliberal characteristics; the rising influence of state capital, especially in the Gulf region, remains underexplored. Qatar is emerging as a key state player in the global food landscape, contesting the dominance of traditional Northern entities by leveraging significant capital to back agribusiness ventures, foster new trade routes, and drive innovation. The study analyzes Qatar Food Security strategies to unpack the interplay between state-driven capitalism, agro-security mercantilism, and agribusiness’s role within the corporate food regime. This study employs a multiple case study methodology on organizations, initiatives, and strategies that have been instrumental to Qatar’s food security response during and after the 2017 economic blockade. The paper concludes that Qatar secures food security through a multifaceted strategy that leverages domestic production, international investments, private sector engagement, and infrastructure development, showcasing its ability to navigate food security amid geopolitical challenges. Qatar adeptly harnessed the private sector to bolster food security in its desert environment and diminish import dependence. This strategic move fortified Qatar’s position as a potent, forward-thinking, and credible state. Over a period, Qatar has emerged as a role model for other Arab and Middle Eastern countries that are facing harsh climate conditions and unruly natural resources that hinder an Agri based economy. This paper endeavors to deeply explore the strategies adopted by this oil rich country to attain self-sufficiency in food and agriculture.